Childhood Vulnerabilities in South Africa: Some Ethical Perspectives - Grobbelaar, Jan; Jones, Chris (African Sun Media, 2021)
This book addresses different challenges that endanger the lives of children in South Africa from an ethical perspective. The text is meant to position itself as a resource for specialists (and practitioners) in ethics and childhood studies. The content is systematically and intersectionally presented, based on scholarly analyses, insights, reasoning, and expertise – originating in different disciplines and backgrounds. It endeavours to help especially those who study the sociocultural contexts of children and families in terms of challenges and opportunities, and for possible support.